2014
DOI: 10.4236/ojemd.2014.46014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Menopausal Sweating and Body Mass Index

Abstract: We sought to examine the relationship between BMI, sweat rate (SR) and sweat volume (SV) in pre-, peri-and postmenopausal women during a moderate exercise. Based on their ages and menstrual cycle history, thirty healthy women were divided into three groups: pre-(22.5 ± 0.8 yrs, n = 10), peri-(46.5 ± 1.1 yrs, n = 10) and post-(52.2 ± 0.9 yrs, n = 10). Participants underwent a 15minute walk on a treadmill at a constant speed of 4.2 km/h at 27˚C. Sweat was collected and measured with a suction apparatus around a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…On the other hand, other studies conducted in the United States (16) and the Netherlands (17) demonstrated a similar association but in perimenopause women only. Other studies have either reported no association between BMI and VMS (18) or have claimed a protective role of BMI (19), supporting the theory that excess adipose tissue is a source of aromatase that converts androstenedione to estrogens (20). We attribute our observed relationship to the thermoregulatory model of hot flashes, which states that in the presence of a narrow hypothalamic thermoneutral zone, the excess adipose tissue acts as a potent insulators preventing any heat dissipation, thereby elevating the core body temperature and precipitating hot flashes (21).…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, other studies conducted in the United States (16) and the Netherlands (17) demonstrated a similar association but in perimenopause women only. Other studies have either reported no association between BMI and VMS (18) or have claimed a protective role of BMI (19), supporting the theory that excess adipose tissue is a source of aromatase that converts androstenedione to estrogens (20). We attribute our observed relationship to the thermoregulatory model of hot flashes, which states that in the presence of a narrow hypothalamic thermoneutral zone, the excess adipose tissue acts as a potent insulators preventing any heat dissipation, thereby elevating the core body temperature and precipitating hot flashes (21).…”
Section: Discussionmentioning
confidence: 85%
“…This association was remained significant after controlled of other risk factors. However, Amabebe showed positive correlation between the high BMI and severity of syndrome [31].…”
Section: Discussionmentioning
confidence: 86%